Mutational landscape of aggressive cutaneous squamous cell carcinoma - Saade, Rami E. (2017)
Purpose: Aggressive cutaneous squamous cell carcinoma (cSCC) is often a disfiguring and lethal disease. Very little is currently known about the mutations that drive aggressive cSCC. Experimental Design: Whole exome sequencing was performed on 39 cases of aggressive cSCC to identify driver genes and novel therapeutic targets. Significantly mutated genes were identified with MutSig or complementary methods developed to specifically identify candidate tumor suppressors based upon their inactivating mutation bias. Results: Despite the very high mutational background caused by UV exposure, 23 candidate drivers were identified including the well-known cancer-associated genes TP53, CDKN2A, NOTCH1, AJUBA, HRAS, CASP8, FAT1, and KMT2C (MLL3). Three novel candidate tumor suppressors with putative links to cancer or differentiation, NOTCH2, PARD3 and RASA1, were also identified as possible drivers in cSCC. KMT2C mutations were associated with poor outcome and increased bone invasion. Conclusions: The mutational spectrum of cSCC is similar to that of head and neck squamous cell carcinoma and dominated by tumor suppressor genes. These results improve the foundation for understanding this disease and should aid in identifying and treating aggressive cSCC.